Calculate the optimum slot area of elliptical microstrip antenna for mobile application - Raad H. Thaher; ِAli Khalid Jassim (Institute of Advanced Engineering and Science, 2019)
Designing and analysis the antenna parameter, for the calculation optimum the slot area for a new broadband elliptical antenna for mobile application, to enhancement impedance bandwidth. Two equations have been obtained, representing the first relationship between the area of the slot and the area of the patch, and the second represents the area of the slot to the wavelength of the band frequency. The antenna was implemented and gets simulation result using CST software and manufacturing on an FR-4 material with =4.3, tan (δ) =0.002 and the feeding line has a characteristic impedance of 50Ω. The proposed antenna is operating in the bandwidth 24GHz and the gain (6.8) dBi.